ENVIRONMENTAL TURBULENCE, PREVIOUS EXPERIENCE, ORGANIZATIONAL CAPACITY FOR CHANGE AND CHANGE PROJECT PERFORMANCE - Sahar Ahmadian; Ali Rastegar; Vahid Malekmohammadi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
There is a growing body of research on the importance of organizational change project performance in the environmental turbulence. However, knowledge about this subject is still limited. To address this gap, this research is an attempt to investigate if environmental turbulence and the previous experience of an organization can influence its capacity for change and influence its performance. To answer this question, a cross-sectional survey was used to gather data for this study. To this purpose, out of 230 experts in one of the organization in Iran, 160 were sent the questionnaires, and data from 156 usable and completed questionnaires were analyzed. The analysis of inferential data was carried out using Partial Least Squares Structural Equation Modeling with the help of Smart PLS software. Finding showed environmental turbulence and its dimensions including intensity, technological turbulence, and market turbulence have a positive effect on organizational capacity for change. Moreover, the previous experience of change affects organizational capacity for change. Data analysis also indicates that this capacity has an effect on the performance of change projects. Different organizations of any size can use the results of this study to increase the performance of change projects.